Cell-penetrable mouse forkhead box protein 3 alleviates experimental arthritis in mice by up-regulating regulatory T cells. (10th May 2015) - Liu, Xia; Ji, Baoju; Sun, Mengyi; Wu, Weijiang; Huang, Lili; Sun, Aihua; Zong, Yangyong; Xia, Sheng; Shi, Liyun; Qian, Hui; Xu, Wenrong; Shao, Qixiang
Summary: Regulatory T cells (Tregs ) have potential applications in clinical disease therapy, such as autoimmune diseases and transplant rejection. However, their numbers are limited. Forkhead box protein 3 (FoxP3) is a key transcription factor that controls Treg development and function. Here, we generated a cell-permeable fusion protein, protein transduction domain (PTD)-conjugated mouse FoxP3 protein (PTD-mFoxP3), and evaluated whether PTD-mFoxp3 can alleviate rheumatoid arthritis (RA) in the collagen-induced arthritis (CIA) mouse model. As expected, PTD-mFoxP3 was transduced into cells effectively, and inhibited T cell activation and attenuated the cell proliferation. It decreased interleukin (IL) 2 and interferon (IFN)-γ expression, and increased IL-10 expression in activated CD4 + CD25 − T cells. PTD-mFoxP3-transduced CD4 + CD25 − T cells attenuated proliferation of activated CD4 + CD25 − T cells. In addition, PTD-mFoxP3 blocked the Th17 differentiation programme in vitro and down-regulated IL-17 production from T cells by modulating induction and levels of retinoid-related orphan receptor gamma t (RORγt). Intra-articular delivery of PTD-mFoxP3 delayed disease incidence remarkably and alleviated autoimmune symptoms of CIA mice. Moreover, protective effects of PTD-mFoxP3 were associated with regulating the balance of T helper type 17 (Th17) and Tregs . These results suggest that PTD-mFoxP3 may be a candidate for RA therapy.